A rare case of Lesch-Nyhan syndrome in adulthood - Zafar, Sharjeel; Shafique, Hira (International Journal of Research in Medical Sciences, 2025)
Lesch-Nyhan syndrome (LNS) is a rare X-linked recessive disorder characterized by hyperuricemia, neurodevelopmental delay, self-mutilation, and gouty arthritis. We present a unique case of a 19-year-old male with a delayed diagnosis of LNS, highlighting the diagnostic challenges associated with adult presentations of this syndrome. The patient exhibited classic symptoms, including severe hyperuricemia, bilateral renal stones, gouty tophi on palms, polyarthralgia, self-injurious behavior, low IQ, delayed motor development, and ataxia. The diagnosis was confirmed through clinical evaluation and biochemical testing, revealing significantly elevated serum uric acid levels. Management included dietary modifications, aggressive hydration, and uricosuric medications, leading to symptomatic improvement. This case underscores the importance of considering LNS in patients with unexplained hyperuricemia and neurobehavioral symptoms. Early diagnosis and appropriate management can improve the quality of life and reduce complications.